A New Asymmetric Fully Homomorphic Encryption Scheme for Cloud Banking Data - Omar, Zana Thalage; Salman Abed, Fadhil; Khamees Ahmed, Shaimaa (Kurdistan Journal of Applied Research, 2021)
Most banks in our time still use the common traditional systems of high cost and relatively slow, we are now in the era of speed and technology, and these systems do not keep pace with our current age, so saving cost and time will be considered a fantastic thing for banks. The way to that is to implement cloud computing strategies with Considering data security and protection when it comes to using the cloud. The best solution to protect data security on the cloud is fully homomorphic encryption systems. The time it takes to encrypt and decrypt data is one of the main barriers it faces. Our current research provides a new algorithm for a publicly-keyed encryption system to keep bank data from tampering and theft when stored on the cloud computing platform, and our new system achieves fully Homomorphic Encryption, which allows mathematical operations to be performed on the encrypted text without the need for the original text. The security of the new system depends on the issue of analyzing huge integers, which reach 2048 bits, to their prime factors, which are considered almost impossible or unsolvable. A banking application has also been created that encrypts the data and then stores it on the cloud. The application allows the user to create accounts and deposits, transfer and withdraw funds, and everything related to banking matters.